Rateless low power listening on TinyOS - Yong, Si Ling (2016)
With the increase in usage of wireless network, power efficiency is becoming a topic of concern. Idling sensor nodes often contribute to power inefficiency and this work explores the implementation of low power listening in sensor nodes to counter the issue. Low power listening reduces power consumption by duty cycling the sensor nodes’ radio between on and off state, as radio signals take up a big portion of battery consumption. This research focuses on the implementation and evaluation of low power listening on the sensor nodes. Through the steps of research, development, testing and evaluation, the implementation of low power listening with rateless codes was completed. The implementation in this work allows rateless codes which is Luby-Transform (LT) codes to run on low power settings efficiently. To evaluate the efficiency of low power listening, voltage readings of individual nodes were monitored and recorded under similar conditions. Experiments conducted shown favourable results; power consumption was reduced by 60.99% in receiver nodes and another 46% in sender nodes. The results obtained show that low power listening can possibly extend the battery lives of sensor nodes. Hence, it is recommended that low power listening gets implemented on more sensor nodes, especially those that need to run unattended for long periods of time.